Revolt in Japan : the young officers and the February 26, 1936 incident - Shillony, Ben-Ami (Princeton legacy library., 1973)
"Revere the Emperor, Destroy the Traitors"-armed with this slogan, on February 26, 1936. Rebellious Japanese troops led by members of the Young Officers' Movement seized the center of Tokyo and murdered several prominent officials. The Young Officers wanted a "Showa Restoration" whereby political and economic power would be restored to the Emperor and people. The privileged classes were to be abolished, wealth redistributed, and the state, rather than big business, was to control the economy. Although the rebellion was suppressed in four days, it dramatized ideological clashes and factional strife within the Imperial Army and the tensions between civil and military authorities.The incident still stirs emotions in Japan and fascinates Japanese writers; Mishima Yukio, the famous novelist who committed suicide by seppuku in 1970, was a great admirer of the Young Officers. This exciting account by Ben-Ami Shillony includes the first full examination of the backgrounds and ideologies of the leaders, and discusses the crucial roles of such figures as the Emperor himself and his brother Prince Chichibu.Originally published in 1973.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.